Pengaruh sleeping bag elektrik terhadap suhu tubuh pada pasien pasca operasi di instalasi bedah sentral - Nafiz, Muhammad Haekal; Mardiyono, Mardiyono; Widigdo, Dwi Ari Murti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Postoperative hypothermia is a common complication in patients undergoing surgery under general anesthesia, characterized by a drop in body temperature below 36°C due to impaired thermoregulation, exposure to cold temperatures, unheated intravenous fluids, and prolonged surgery. Globally, its incidence reaches 5–15% and can lead to serious complications such as coagulation disorders, surgical site infections, prolonged recovery, and increased mortality. Prevention is achieved through warming intravenous fluids, the use of heating blankets, and continuous body temperature monitoring. An innovative electric sleeping bag is currently being developed as a more effective method for maintaining stable patient body temperature, increasing comfort, accelerating recovery, and reducing the risk of postoperative hypothermia. Purpose: To determine the effect of an electric sleeping bag on body temperature in postoperative patients. Method: This quantitative study, using a Research and Development (R&D) approach, was conducted at Assyifa Islamic Hospital in Sukabumi City. The study population consisted of 244 patients over the past five months, with a sample of 42 participants divided into intervention and control groups, each with 21 participants, and calculated using a simple random sampling technique. Data analysis was performed using a paired t-test to determine differences between the pretest and posttest. Results: Statistical analysis using a paired sample t-test showed that in the intervention group, the p-value was 0.000 (p < 0.05), indicating a significant effect of the electric sleeping bag on increasing the body temperature of postoperative patients. Conversely, in the control group, the p-value was 0.329 (p > 0.05), indicating no significant effect on changes in patient body temperature. Conclusion: The electric sleeping bag affected the increase in body temperature in postoperative patients in the intervention group (p-value 0.000), while there was no significant effect in the control group (p-value 0.329). Keywords: Body Temperature; Electric Sleeping Bag; Hypothermia; Postoperative Patients. Pendahuluan: Hipotermia pascaoperasi adalah komplikasi umum pada pasien yang menjalani pembedahan dengan anestesi umum, ditandai oleh penurunan suhu tubuh di bawah 36°C akibat gangguan termoregulasi, paparan suhu dingin, cairan infus tidak dipanaskan, dan lamanya operasi. Secara global, insidensinya mencapai 5–15% dan dapat menimbulkan komplikasi serius seperti gangguan koagulasi, infeksi luka operasi, perpanjangan pemulihan, serta peningkatan mortalitas. Pencegahan dilakukan melalui pemanasan cairan infus, penggunaan selimut pemanas, dan pemantauan suhu tubuh secara kontinu. Inovasi sleeping bag elektrik kini dikembangkan sebagai metode yang lebih efektif untuk menjaga kestabilan suhu tubuh pasien, meningkatkan kenyamanan, mempercepat pemulihan, dan menurunkan risiko hipotermia pascaoperasi. Tujuan : Untuk mengetahui pengaruh sleeping bag elektrik terhadap suhu tubuh pada pasien pasca operasi. Metode: Penelitian kuantitatif dengan pendekatan Research and Development (R&D), dilakukan di Rumah Sakit Islam (RSI) Assyifa Kota Sukabumi. Populasi penelitian berjumlah 244 pasien selama lima bulan terakhir dengan sampel 42 partisipan yang dibagi menjadi kelompok intervensi dan kontrol, masing-masing 21 partisipan dan dihitung menggunakan teknik simple random sampling. Analisis data dilakukan dengan uji Paired T-Test untuk melihat perbedaan pretest dan posttest Hasil: Uji statistik menggunakan Paired Samples Test menunjukkan bahwa, pada kelompok intervensi nilai p-value sebesar 0.000 (p < 0.05), sehingga ditemukan adanya pengaruh signifikan sleeping bag elektrik terhadap peningkatan suhu tubuh pasien pascaoperasi. Sebaliknya, pada kelompok kontrol diperoleh p-value sebesar 0.329 (p > 0.05), menunjukkan tidak adanya pengaruh signifikan terhadap perubahan suhu tubuh pasien. Simpulan: Sleeping bag elektrik berpengaruh terhadap peningkatan suhu tubuh pasien pascaoperasi pada kelompok intervensi (p-value 0.000), sedangkan tidak ada pengaruh yang signifikan pada kelompok kontrol (p-value 0.329). Kata Kunci: Hipotermia; Pasien Pascaoperasi; Sleeping Bag Elektrik; Suhu Tubuh.